Financial contagion with spillover effects: a multiplex network approach - Gustavo Peralta; Ricardo Crisóstomo (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
This paper presents a comprehensive model of financial contagion encompassing both direct and indirect transmission channels. We introduce direct contagion through a 2-layered multiplex network to account for the distinct dynamics resulting from collateralized and uncollateralized transactions. Moreover, the spillover effects of fire sales, haircut prociclicality and liquidity hoarding are specifically considered through indirect transmission channels. This framework allows us to analyze the determinants of systemic crisis and the resilience of different financial network configurations. Our first experiment demonstrates the benefits of counterparty diversification as a way of reducing systemic risk. The second experiment highlights the positive effect of higher initial capital and liquidity levels, while stressing the potentially counterproductive impact of rapidly increasing the minimum capital and liquidity ratios, particularly in times of stress. The third experiment examines the possibility of controlling the maximum haircut rates, although the impact of this measure is modest compared to other alternatives. Finally, our last experiment evidences the fundamental role played by fire sales and market liquidity in either leading or mitigating systemic crises.
Keywords: C63; D85; G01; G18; 330; Multiplex networks; financial contagion; spillover effects; financial regulation; systemic risk; simulations